PENGGUNAAN LAYANAN BIMBINGAN KELOMPOK TEKNIK DISKUSI UNTUK MENGURANGI KENAKALAN REMAJA SISWA - Eka Lisdiana; Giyono Giyono; Ratna Widiastuti (ALIBKIN (Jurnal Bimbingan Konseling), 2013)
The purpose of this research was to reduce juvenile delinquency by using group guidance service technical discussion in students of Class XI SMK SPP Lampung school year 2012/2013. The problem in this research was juvenile delinquency students. The problem in this research was “whether juvenile delinquency can be reduced by using group guidance service technical discussion?”. The methods used in this research was experimental methods by design one-group pretest-posttest. Subject in research students which showed juvenile delinquency high which totaled 6 (six) students. Data collection techniques in this research used observation guidlines. The results obtained in the research indicate that juvenile delinquency can be reduced to the students using group guidance services discussion technique, based on the calculation of the 5% significance test scored p = 0.027, p 0.05. Ha thus received, that juvenile delinquency can be reduced to the students using group guidance services discussion techniques. The conclusion of this research was juvenile delinquency can be reduced using group guidance services discussion techniques in class XI in SMK SPP Lampung Year 2012/2013. The advices which can be suggested were (1) who the subject should be confident and encourage self-esteem in order to show positive attitude in the environment. (2) BK teachers should conduct group guidance services discussion technique in solving juvenile delinquency. (3) To the researchers, should be able to do research on juvenile delinquency with involving the needs of self esteem.Kata kunci: bimbingan konseling, kenakalan remaja, layanan bimbingan kelompok.